Dynamics of Compensation and Job Rotation: The Key to Improving Performance in the Serang City Regional Government Environment - Ramadhan, TB Guruh; Arifin, Yusuf; Hamsinah, Hamsinah; Tirtosetianto, Raden Hario; Sunarsi, Denok (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
This research aims to analyze the effect of compensation and work rotation on employee performance in the Regional Government of Serang City. Data collection was carried out with samples using Google Form and questionnaires, with a total of 74 respondents. The sampling technique used in the research was random proposal sampling. Data analysis was carried out using the Structural Equation Modeling (SEM) method, with a variance-based approach using the Smart Partial Least Square (SmartPLS) application. The results of this research show that compensation has a positive and significant effect on employee performance, and work rotation has a positive and significant effect on employee performance in the local government environment.